2007
DOI: 10.1097/01.tp.0000269113.59857.d6
|View full text |Cite
|
Sign up to set email alerts
|

Mediators Involved in the Immunomodulatory Effects of Apoptotic Cells

Abstract: Immunomodulatory properties are attributed to apoptotic cells. These properties have been used to modulate allogeneic immune responses in experimental transplantation settings. In independent studies, apoptotic cell infusion has been shown to favor hematopoietic cell engraftment, to increase heart graft survival, and to delay the lethal onset of graft-versus-host disease (GVHD). The goal of this review was to discuss how apoptotic cell infusion interferes with graft rejection or host rejection (i.e., GVHD) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…Several studies have found that apoptotic cells exhibit a dramatic immunosuppressive effect in vivo (6,43,44). Our studies with heart transplantation showed that a single injection of apoptotic cells could extend successful engraftment for Ͼ40 days on the average.…”
Section: Discussionmentioning
confidence: 68%
“…Several studies have found that apoptotic cells exhibit a dramatic immunosuppressive effect in vivo (6,43,44). Our studies with heart transplantation showed that a single injection of apoptotic cells could extend successful engraftment for Ͼ40 days on the average.…”
Section: Discussionmentioning
confidence: 68%
“…In contrast to PDC isolated from healthy volunteers or to the GEN2.2 PDC cell line, EMP did not induce significant Mo-DC maturation and, in this setting, reduced lipopolysaccharide-induced IL-12 secretion, as observed after incubation with apoptotic cells. 9,38 Furthermore, microparticles derived from activated T cells or platelets did not induce PDC maturation. Lastly, PDC maturation induced by EMP required an active uptake mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various circulating microparticles, platelet-derived microparticles are the most abundant in the bloodstream, representing between 70 to 90% of circulating microparticles in healthy subjects. 8 As shown for apoptotic bodies 9 -another form of cell dust or debris, tumor-or fibroblast-derived microparticles captured by monocytes may induce regulatory cytokine secretion. 10 In addition, microparticles from activated T cells can deliver differentiation signals to stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…A poptotic cells exert immunomodulatory properties (1)(2)(3). This occurs through the release of immunosuppressive cytokines by apoptotic cells themselves during the apoptotic process (4) as well as indirectly via cells uptaking apoptotic cells (5,6).…”
mentioning
confidence: 99%